Proposed new interior design scheme kid's nursery for Koperasi of UiTM Perak at Universiti Teknologi MARA, Seri Iskandar Campus, 32610 Seri Iskandar, Perak / Nuraisha Md Idris - Md Idris, Nuraisha (Faculty of Architecture, Planning and Surveying, 2011)
Final student in Diploma Architecture needs to come out with project report in order to understand the whole final project in every aspects started from basic level to final presantatation. Project report is one of the subject that had to be taken by students semester 6 (06) in Diploma Interior Design. In this project report, to produce a successful design, the process of designing should be based upon detailed research and observation and every aspect should be identified. The final project proposal can be two types and it is proposed new interior design or proposed upgrading interior design. The final project proposal that has been chosen for this final semester is PROPOSED NEW INTERIOR DESIGN SCHEME FOR KID’S NURSEY FOR KOPERASI UITM SERI ISKANDAR, PERAK. This project is being proposed according to the projects goal and client requirement. The main objective is to design a nursery with a suitable concept, design and requirement in order to give the childrens to make feel ecsiting and enjoy to come nursery. The process to complete this project is being held according to the design stage, it is starting with project brief, research and analysis, till lastly proposal design. In conclusion this proposal is the new design scheme which make the design process need to be research in every aspect require.